Objects of Verification of the Constitutionality of Legal Acts in the Constitutional Court of the Republic of Lithuania - Pūraitė-Andrikienė, Dovilė (Teisė, 2020)
This article analyzes the objects of verification of the constitutionality of legal acts in the Constitutional Court of the Republic of Lithuania. This article aims to reveal the development of the official constitutional doctrine of the Constitutional Court on the issue of objects (according to the different breakdowns of this doctrine highlighted in the article) of verification of the constitutionality of legal acts, which are entrenched in the Articles 102 and 105 of the Constitution of the Republic of Lithuania, and the further development of this institute inter alia in light of the 2019 amendment to the Constitution, which introduced a mechanism for lodging an individual constitutional complaint.